ответ: 2м/с
Объяснение:
Дано:
x=t²-2t+1
t=2c
V-?
Скорость равна первой производной от пути:
V=(x)'=(t²-2t+1)'=2t-2
Подставляем значение t=2c и получим:
V=2*2-2=2м/с
Уравнение движения
x(t)=xo + vo*t + (a/2)*t²
x(t)=1 - 2*t + (2/2)*t²
a=2 м/с²; vo=-2 м/с
v(t)=vo + at
v(t)=-2 + 2*t
v(2)=-2 + 2*2
v(2)=2 м/с.
v(t)=x'=2t - 2
v(2)=2*2 - 2=4 м/с.
ответ: 2м/с
Объяснение:
Дано:
x=t²-2t+1
t=2c
V-?
Скорость равна первой производной от пути:
V=(x)'=(t²-2t+1)'=2t-2
Подставляем значение t=2c и получим:
V=2*2-2=2м/с
Уравнение движения
x(t)=xo + vo*t + (a/2)*t²
x(t)=1 - 2*t + (2/2)*t²
a=2 м/с²; vo=-2 м/с
v(t)=vo + at
v(t)=-2 + 2*t
v(2)=-2 + 2*2
v(2)=2 м/с.
v(t)=x'=2t - 2
v(2)=2*2 - 2=4 м/с.